A rare case of transient left ventricular apical ballooning syndrome following living donor liver transplantation: A case report and literature review. (2019) - Tanaka, Asuka; Onoe, Takashi; Ishiyama, Kohei; Ide, Kentaro; Tashiro, Hirotaka; Ohdan, Hideki
Highlights: Transient Left Ventricular Apical Balloon Syndrome (LV-ABS) is an acute dysfunction of the left ventricle. Its clinical feature is similar to myocardial infarction. The echocardiogram show characteristic finding which is different from that of myocardial infarction. LV-ABS is rare, however, should be considered after liver transplantation. Proper diagnosis is important to restore cardiac function although it improve almost normally with conservative treatment. Abstract: Introduction: Transient Left Ventricular Apical Balloon Syndrome (LV-ABS) is an unknown acute dysfunction of the left ventricle, which develops under emotional or physical stress events like the major surgical postoperative period. Presentation of case: A 68-year-old woman diagnosed with hepatitis C cirrhosis was admitted for living donor liver transplantation (LDLT). No evidence for underlying cardiac or pulmonary disease was found. LDLT was performed, and her intra and post-operative course was uneventful. On post-operative day 4, dyspnea and tachycardia were observed. Echocardiography showed a severe wall motion abnormality with ballooning of the apex with normal basilar wall motion and a severely impaired left ventricular function with an ejection fraction (EF) of 40%. Blood tests showed greatly increased level of N-terminal pro-brain natriuretic peptide (NT- pro BNP). Evidence of significant ischemic heart disease was not obtained and a transient LV-ABS was diagnosed. Although she required intensive care, her cardiac function became normal by conservative treatment. Discussion: Transient LV-ABS has been reported to occur more frequently in post-menopausal women with reduced estrogens reported to protect myocardium from sympathetic stress after mental or physical stress events. It has been suggested that this disease arises from myocardial stunning with high levels of circulating catecholamines and stress related neuropeptides. However, even in a serious condition, cardiac function has recovered normally in all cases by appropriate care. Conclusion: Transient LV-ABS is one cause of cardiac dysfunction after LDLT, and it is important to strictly manage cardiac function when diagnosed as transient LV-ABS.